The Analysis of the contextual meaning Expression of the word ‘Cry’ from the Children’s book written by Enid Blyton - Paulina Novarita; Wahyu Satya Gumelar; Syifa Sonia (Institut Agama Islam Negeri Palopo, 2025)
This study aims to analyze the contextual meaning of the word